1973
DOI: 10.1002/cne.901480204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the cortical degeneration in the visual regions of the temporal lobe of the monkey following section of the anterior commissure and the splenium

Abstract: The patterns of degeneration in the visual centers of the temporal lobe of the rhesus monkey following section of the anterior commissure and the splenium of the corpus callosum have been compared. Both commissural systems distribute interhemispheric fibres to the anterior part of the inferior temporal neocortex whereas the posterior part receives commissural fibres predominantly from the splenium.There were hints that the temporal visual neocortex may be further subdivided into discrete areas since the degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The septal nuclei, the fornix, and the underlying diencephalic structures were spared. This surgery disconnected the anterior temporal cortex of each hemisphere from the other, since most commissural fibers of this area traverse the AC rather than the corpus callosum (20)(21)(22). After recovery, the monkey was trained with a set (set A) of the paired associates to the criterion performance level, and then extracellular spike discharges of single neurons were recorded as a prelesion control in the anterior IT cortex (9,23,24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The septal nuclei, the fornix, and the underlying diencephalic structures were spared. This surgery disconnected the anterior temporal cortex of each hemisphere from the other, since most commissural fibers of this area traverse the AC rather than the corpus callosum (20)(21)(22). After recovery, the monkey was trained with a set (set A) of the paired associates to the criterion performance level, and then extracellular spike discharges of single neurons were recorded as a prelesion control in the anterior IT cortex (9,23,24).…”
Section: Resultsmentioning
confidence: 99%
“…We combined single-unit recording techniques with surgical manipulations in the monkey. First, the AC of the monkeys was cut to remove influences upon anterior IT neurons from those in the other hemisphere (20)(21)(22). Behaviorally, the monkeys fixated the stimuli and learned the pair-association task quite normally, just as in the previous study (9).…”
Section: Discussionmentioning
confidence: 99%
“…Although similar functions are performed by the corpus callosum, cortical areas served by these two commissures have in some cases been found to be distinct (58). The unique use of the anterior commissure as an extracallosal commissural pathway would probably not provide the level of compensation generally seen in acallosals, and it seems likely that the use of several other commissures is also enhanced (35).…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, we found that the distribution of callosal projection cells is very similar to that of callosal fiber terminations and thus reflects topographic organization to the same degree in various regions of cortex. The major dissimilarity in callosal inputs versus outputs is in inferotemporal cortex: this region receives inputs via the corpus callosum and, in its anterior portion, via the anterior commissure (Zeki, 1973), but its projections to the contralateral hemisphere pass predominantly through the anterior commissure and not the corpus callosum (Jouandet and Gazzaniga, 1979;Hamilton, 1982; see Fig. 10).…”
Section: Discussionmentioning
confidence: 99%
“…Within IT, however, there are regional differences in architecture (Seltzer and Pandya, 1978), connections (Zeki, 1973;Seltzer and Pandya, 1978;Desimone et al, 1980), and receptive field size (Desimone and Gross, 1979), suggesting that there may be more than one functionally distinct subdivision of this region. Posterior parietal cortex (area 7, or PG and PE) occupies much of callosal recipient zone 6 (Lynch et al, 1977;Robinson et al, 1978).…”
Section: A Standard Representation Of Callosal Projectionsmentioning
confidence: 99%